Hydroalcoholic Extract and Ethyl Acetate Fraction of Bixa orellana Leaves Decrease the Inflammatory Response to Mycobacterium abscessus Subsp. massiliense. (2nd October 2018) - Lima Viana, José; Zagmignan, Adrielle; Lima Lobato, Luís Felipe; Gomes Abreu, Afonso; da Silva, Luís Cláudio Nascimento; Sá, Joicy Cortez de; Monteiro, Cristina de Andrade; Lago, João Henrique Ghilardi; Gonçalves, Letícia Machado; Carvalho, Rafael Cardoso; Neto, Lídio Gonçalves Lima; de Sousa, Eduardo Martins
Abstract : The incidence of infections caused by rapidly growing mycobacteria (RGM), especially Mycobacterium abscessus subsp. massiliense ( Mabs ), is increasing worldwide. Severe infections are associated with abscess formation and strong inflammatory response. This study evaluated the antimicrobial and anti-inflammatory activities of a hydroalcoholic extract (BoHE) and ethyl acetate fraction (BoEA) of Bixa orellana leaves. Antimicrobial activity was evaluated by broth microdilution to determine the minimum inhibitory (MIC) and the minimum bactericidal (MBC) concentrations. Cytotoxicity was evaluated using erythrocytes and RAW 264.7 cells. Nitric oxide (NO) was assayed in stimulated RAW 264.7 cells, and inflammatory cell migration and acute toxicity were evaluated in a Mabs -induced peritonitis mouse model. The compounds present in BoEA were identified by high performance liquid chromatography and mass spectrometry (HPLC-MS). The MIC and MBC values were 2.34 mg/mL and 37.5 mg/mL for BoHE and 0.39 mg/mL and 6.25 mg/mL for BoEA. The extracts did not induce significant toxicity in erythrocytes and RAW 264.7 cells. High levels of NO induced by Mabs were decreased by treatment with both extracts. The anti-inflammatory activity was confirmed in vivo by significant reduction of the cell migration to the peritoneum following BoHE and BoEA pretreatment. Animals treated with BoHE or BoEA did not show signs of acute toxicity in stomach, liver, and kidney. The chemical characterization of BoEA (the most active extract) revealed that kaempferol-3-O-coumaroyl glucose is its major component. The extract of B. orellana may be effective for treating infections caused by Mabs.